2005
DOI: 10.1097/01.mph.0000149251.68562.8e
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Carcinoma in Children, Adolescents, and Young Adults

Abstract: The authors conducted a retrospective evaluation of patients younger than 30 years with colorectal carcinoma in Argentina. Patients were divided into group 1 (patients treated at pediatric institutions from 0 to 20 years of age, n = 14) and group 2 (patients from 21 to 30, n = 7, treated at adult centers). Group 1 had significantly more advanced disease and a poorer prognosis. Six patients (2/14 in group 1 and 4/7 in group 2) survive disease-free. Thirteen patients died of progressive disease, 1 died of a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 7 publications
3
38
1
5
Order By: Relevance
“…El cuadro clínico de presentación puede incluir anemia, dolor abdominal, sangrado digestivo bajo (proctorragia), pérdida de peso y cambios en los hábitos evacuatorios. [2][3][4] Anatómicamente, puede presentarse con igual frecuencia tanto en el colon derecho como izquierdo, con tendencia al crecimiento exofítico e invasión de la muscularis mucosae. Los ganglios linfáticos regionales, el hígado, los pulmones y los …”
Section: Discussionunclassified
See 1 more Smart Citation
“…El cuadro clínico de presentación puede incluir anemia, dolor abdominal, sangrado digestivo bajo (proctorragia), pérdida de peso y cambios en los hábitos evacuatorios. [2][3][4] Anatómicamente, puede presentarse con igual frecuencia tanto en el colon derecho como izquierdo, con tendencia al crecimiento exofítico e invasión de la muscularis mucosae. Los ganglios linfáticos regionales, el hígado, los pulmones y los …”
Section: Discussionunclassified
“…[1][2][3][4] El tratamiento oncológico dependerá del estadio al momento del diagnóstico y requerirá, en general, la remoción del tumor junto con el pedículo vascular que lo irriga y los ganglios linfáticos regionales en un bloque. En algunos casos, además, será necesario el tratamiento quimioterápico neoadyuvante.…”
Section: Colorectal Adenocarcinoma In a 5 Year Old Girlunclassified
“…O câncer colorretal é classicamente considerado como doença de indivíduos idosos, com pico de incidência na sexta década de vida [7][8][9] . Mais de 90% de todos casos de câncer de cólon e reto ocorrem em pacientes maiores de 50 anos 3,10 .…”
Section: Discussionunclassified
“…An investigation from Taiwan (28 patients 20 years old or less) demonstrated that proportion of mucinous adenocarcinoma was higher than that in the older population and that most cases were advanced at diagnosis (Dukes stages C or D), with an overall survival rate of only 21 % (Chen et al 2001). In a study of Argentina, patients with CRC of the group covering 0-20 years of age revealed a high-risk group in comparison with older patients, in that this group had significantly more advanced disease and poorer prognosis (Chantada et al 2005). In a subset of patients with CRC younger than 18 years, six out of seven had tumor progression or relapse, and five died of their tumor (Ferrari et al 2008).…”
Section: Liver Metastases In Pediatric Colorectal Carcinomamentioning
confidence: 94%